Hybrid vigour for thermal tolerance in hybrids between the allopatric kelps Laminaria digitata and L. pallida (Laminariales, Phaeophyceae) with contrasting thermal affinities. Issue 4 (2nd October 2019) - Martins, Neusa; Pearson, Gareth A.; Gouveia, Licínia; Tavares, Ana I.; Serrão, Ester A.; Bartsch, Inka
ABSTRACT: Kelps are globally important bioengineering species with high ecological and economic value, but are increasingly threatened by climate-driven geographic range shifts. The inheritance of economically important traits from parents to offspring is poorly understood in kelps but it is of utmost interest to seaweed farmers wishing to select strains with superior performance and resilience to environmental change. For two allopatric kelp species (N-Atlantic Laminaria digitata and S-Atlantic L. pallida ), we compared the speed of gametogenesis and reproductive success in parental gametophytes, and produced intraspecific and reciprocal interspecific crosses of female × male gametophyte parents isolated from the two species. We then compared the upper thermal resilience of microscopic and macroscopic sibling sporophytes in an exposure experiment over two weeks. The upper thermal limit of the sporophytes resulting from intraspecific crosses of the two species deviated by 1°C. In contrast, sporophytes from both interspecific hybrid crosses had a 2–3°C higher upper thermal tolerance than single species sporophytes, indicating heterosis for thermal tolerance. This phenotypic response appears partially sex-dependent in our study, with female parents being more important in determining the thermal-response phenotype than male parents. The presence of male gametophytes generally enhanced female reproductive success. Both gametogenesis rate and reproductive success differed among the types of reciprocal crosses. Although the interspecific crosses were artificial in an ecological sense, they may provide a tool for understanding the molecular basis of heterosis and thermal tolerance in kelps (e.g. by investigating species-specific gene expression), or for aquaculture breeding programmes against a background of rapid environmental change.